Linking accretionary orogenesis with supercontinent assembly - Cawood P.A.; Buchan C. (My University, 2007)
Age relations for assembly ofGondwana and Pangea indicate that the timing of collisional orogenesis between amalgamating continental bodies was synchronous with subduction initiation and contractional orogenesis within accretionary orogens located along the margins of these supercontinents. Final assembly of Gondwana occurred between c.570 and 510 Ma, amalgamating the various components of East and West Gondwana. This was coeval with a switch from passive margin sedimentation to convergent margin activity along the Pacific margin of the supercontinent. Timing of subduction initiation along the Pacific margin ranges from 580 to 550Ma as evidenced by the first appearance of arc derived detrital zircons in the upper Byrd Group sediments and the oldest supra-subduction zone plutons along the Antarctic segment of themargin.Aphase of extensionmarked by supra-subduction zone ophiolite generation at 535–520Ma is preserved in greenstone successions in eastern Australia and overlaps the onset of Ross–Delamerian contractional orogenesis between 520 and 490Ma, inboard of the plate margin that coincides with the cessation of collisional orogenesis between the amalgamating blocks of Gondwana. Supra-subduction zone igneous activity was continuous throughout this period indicating that subduction was ongoing.
Keywords: Accretionary Orogen; supercontinents; driving mechanisms; Gondwana; Pangea; plate reorganization